Giant breast malignant phyllodes tumor: a case report and literature review - Ostapenko, Valerijus; Ostapenko, Andrejus; Dasevičius, Darius; Ostapenko, Edvinas (Lietuvos chirurgija, 2016)
Introduction Phyllodes tumors of the breast are rare and account for less than 1% of breast tumors. They occur over a wide age range with a median age of 45 years. Malignant transformation of a phyllodes tumor is a rare form of breast cancer accounting for just 0.5% of all breast cancers. A simple mastectomy is performed for giant phyllodes tumors (>10 cm), those that are multifocal, in cases of malignant phyllodes tumors, in cases of recurrence or in phyllodes of ‘borderline’ histology Case report We report a rare case of a rapidly growing malignant giant phyllodes tumor of the young, 26 year-old white woman, who underwent successful combined treatment nipple-sparing mastectomy and irradiation in National Cancer Institute, Vilnius, Lithuania Conclusions Multidisciplinary approach and modern imaging studies allows us to diagnose and successfully treat this rare pathological state. Scientific trials to delineate proper indications for combined treatment malignant phyllodes tumor of the young patients are needed.